18F-FDG PET/CT Imaging: Normal Variants, Pitfalls, and Artifacts Musculoskeletal, Infection, and Inflammation - Mbakaza, Olwethu; Vangu, Mboyo-Di-Tamba Willy (Frontiers in Nuclear Medicine, 2022)
F-18 FDG PET/CT is an integral part of modern-day practice, especially in the management of individuals presenting with malignant processes. The use of this novel imaging modality in oncology has been rapidly evolving. However, due to its detection of cellular metabolism, it is not truly tumour specific. F-18 FDG is also used in the detection of infective and inflammatory disorders. One of the challenges experienced with F-18 FDG PET/CT imaging is the correct differentiation of abnormal uptake that is potentially pathologic, from physiological uptake. Imaging readers, particularly the nuclear physicians therefore need to be aware of normal physiological variants of uptake, as well as potential pitfalls and artifacts when imaging with F-18 FDG. This is true for musculoskeletal uptake, where more than often, infective, and inflammatory processes should not be mistaken for malignancy. This article aims to provide a pictorial review and analysis of cases that depict musculoskeletal, infective, and inflammatory uptake as normal variants, pitfalls, and artifacts on F-18 FDG PET/CT imaging. The ultimate intent of this article is to minimize poor imaging interpretation and limit potential misdiagnoses that may impact of the management of patients with undesirable consequences.